Experimental and Numerical Investigations of the Hydraulic Characteristics of the Makhool Dam in Iraq: A Review - Sadiq, Fatima Ali; Alaa Hussein , Haitham; Mohd Arif Zainol, Mohd Remy Rozainy (Al-Nahrain Journal for Engineering Sciences, 2025)
The hydraulic characteristics of dams can be predicted with high precision and reliability of physical and numerical models depending on accurate hydraulic data. The model is operated and simulated to get a more efficient, optimized utilization of the dam. This research included a comprehensive overview and literature examination of the Makhool Dam which is considered one of the most important dams under construction in Iraq. Previous studies of the dam focused on different topics in the operation of the dam and analyses of its properties, part of which focused on the dam ability to manage flood and how it works best with other dams in critical times, and another part studied the properties of the stilling basin, velocity in the dam reservoir, pressure, seepage and other characteristics that affect the operating the dam. Despite this research and the variety of topics discussed, there is no well-established research on the operation of the bottom and emergency spillway of the dam by using computational fluid dynamics (CFD) simulation software. CFD is considered an essential tech because it has an important influence in determining the hydraulic properties of a spillway and studying its effectiveness under different operating conditions. Because the spillway is an important element in the dam body, the research highlighted the necessity of performing a simulation using appropriate CFD software for this part. This research has also reviewed previous research on CFD software and their ability to simulate previously constructed or under-construction dams to analysis of its hydraulic properties.